Osteogenic differentiation of adipose-derived canine mesenchymal stem cells seeded in porous calcium-phosphate scaffolds - Herrera, David; Lodoso-Torrecilla, Irene; Ginebra, Maria-Pau; Rappe, Katrin; Franch, Jordi (Frontiers in Veterinary Science, 2023)
Engineered bone graft substitutes are a promising alternative and supplement to autologous bone grafts as treatments of bone healing impairment. Advances in human medicine extend an invitation to pursue these biomimetic strategies in animal patients, substantiated by the theory that specialized scaffolds, multipotent cells and biological cues may be combined into a bioactive implant intended for the enhancement of tissue regeneration. This proof-of-concept study was designed to evaluate and validate beta-tricalcium phosphate foam scaffolds seeded with canine mesenchymal stem cells derived from adipose tissue. Cell-inoculated samples and sham controls were cultured in a static fashion for 72 hours in complete growth medium to evaluate seeding capacity, while a subset of loaded scaffolds was further induced with osteogenic culture medium for 21 days. Produced implants were characterized and validated with a combination of immunofluorescence and reflection confocal microscopy, scanning electron microscopy and polymerase chain reaction to confirm osteogenic differentiation in tridimensional-induced samples. After 72 hours of culture, all inoculated scaffolds presented widespread yet heterogeneous surface seeding, distinctively congregating stem cells around pore openings. Furthermore, at 21 days of osteogenic culture conditions, robust osteoblastic differentiation of the seeded cells was confirmed by the change of cell morphology and clear deposition of extra-cellular matrix, accompanied by mineralization and scaffold remodeling; furthermore, all induced cell-loaded implants lost specific stemness immunophenotype expression and simultaneously upregulated genomic expression of osteogenic genes Osterix and Ostecalcin.